The Learning Outcome Improvement of Quadratic Function with NHT-Type Cooperative Learning Assisted by Geogebra and Flipbook - Azzahroh, Fita Fatimah; Nikmah, Anna Royyana; Kriswandani, Kriswandani (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This Collaborative Classroom Action Research (PTKK) aims to improve learning outcomes of quadratic functions through the NHT (Number Head Together) cooperative learning model assisted by geogebra and flipbooks for class X-5 students of SMA N 3 Salatiga. The subjects of this study were students of class X-5 with a total of 34 students consisting of 11 male students and 23 female students. PTKK consists of two cycles, namely Cycle I and Cycle II, each consisting of four stages: planning, action, observation, and reflection. Data collection techniques in this study used student learning outcomes tests and observations during the learning process in cycles I and II. The research instrument used was a description test consisting of 3 questions for each cycle and learning observations, which consisted of the learning process and students' responses to learning. The data analysis techniques used consisted of two types, namely descriptive qualitative methods and descriptive statistics. The study's results showed that using the NHT learning model with the help of GeoGebra and flipbooks can improve student learning outcomes. This is indicated by the percentage of classical completeness, which also increased from the pre-cycle of 67.65%. In the first cycle, it increased to 73.53%; in the second, it increased to 91.18%. This shows that the use of media can make a big contribution to the world of education.